Nine perfect strangers - Moriarty, Liane (New York : Flatiron Books, 2018)
Nine people gather at a remote health resort. Some are here to lose weight, some are here to get a reboot on life, some are here for reasons they can't even admit to themselves. Amid all the luxury and pampering, the mindfulness and meditation, they know these ten days might involve some real work. But none of them could imagine just how challenging the next ten days are going to be. Frances Welty, the formerly bestselling romantic novelist, arrives at Tranquillum House and is immediately intrigued by her fellow guests, including the charismatic owner and director. Could this person really have the answers Frances didn't even know she was seeking? Should Frances put aside her doubts and immerse herself in everything Tranquillum House has to offer -- or should she run while she still can? And it's not long before every guest is asking the same question.
Keywords: Novelists -- Fiction; Health resorts -- Fiction; Strangers -- Fiction; Interpersonal relations -- Fiction; City dwellers -- Fiction; Thrillers (Fiction.); Psychological fiction; Fiction; Psychological fiction; Thrillers (Fiction); Suspense fiction; Psychological fiction; Thrillers (Fiction)